Difficulties of learning the French language among first-year students at the Hotel Technical Institute in Lattakia - Ibrahim, Pascale; Fouad Khouri (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Psychology is concerned with the concept of learning difficulties, yet we talk in educational and educational literature about university failure more than we talk about learning difficulties. Our study aims to understand and identify the difficulties of learning the French language in order to improve the educational process and help students develop their language learning process. Therefore, the question of this research address the identification of the type of difficulties, whether they are linguistic or psychological, and to study the nature of these difficulties, whether they are external or internal. And, finally, how to determine the difficulties of learning the French language among first-year students at the Hotel Technical Institute in Lattakia.